Cody

# Problem 415. Sum the Infinite Series

Solution 1602247

Submitted on 6 Aug 2018 by Jonas Nockert
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

### Test Suite

Test Status Code Input and Output
1   Pass
x = 1; [c,s] = infinite_series(x); c_correct = -0.3800580037051224; s_correct = 0.3845865774434312; assert(abs(c-c_correct)<50*eps & abs(s-s_correct)<50*eps)

fs = function_handle with value: @(x)0.5i*exp(-i*x)*(-1+exp(i*x))*(-exp(i*x)+exp(i*x)*log(1-exp(i*x))+log(exp(-i*x)*(-1+exp(i*x)))-1)

2   Pass
x = exp(1); [c,s] = infinite_series(x); c_correct = 0.2832904461013926; s_correct = -0.2693088098978689; assert(abs(c-c_correct)<50*eps & abs(s-s_correct)<50*eps)

fs = function_handle with value: @(x)0.5i*exp(-i*x)*(-1+exp(i*x))*(-exp(i*x)+exp(i*x)*log(1-exp(i*x))+log(exp(-i*x)*(-1+exp(i*x)))-1)

3   Pass
x = sqrt(3); [c,s] = infinite_series(x); c_correct = -0.3675627321761342; s_correct = -0.2464611942058812; assert(abs(c-c_correct)<50*eps & abs(s-s_correct)<50*eps)

fs = function_handle with value: @(x)0.5i*exp(-i*x)*(-1+exp(i*x))*(-exp(i*x)+exp(i*x)*log(1-exp(i*x))+log(exp(-i*x)*(-1+exp(i*x)))-1)

4   Pass
x = 0.001; [c,s] = infinite_series(x); c_correct = 0.9984257500575904; s_correct = 0.0079069688545917; assert(abs(c-c_correct)<50*eps & abs(s-s_correct)<50*eps)

fs = function_handle with value: @(x)0.5i*exp(-i*x)*(-1+exp(i*x))*(-exp(i*x)+exp(i*x)*log(1-exp(i*x))+log(exp(-i*x)*(-1+exp(i*x)))-1)

5   Pass
x = pi/4; [c,s] = infinite_series(x); c_correct = -0.2042534159513846; s_correct = 0.5511304391316155; assert(abs(c-c_correct)<50*eps & abs(s-s_correct)<50*eps)

fs = function_handle with value: @(x)0.5i*exp(-i*x)*(-1+exp(i*x))*(-exp(i*x)+exp(i*x)*log(1-exp(i*x))+log(exp(-i*x)*(-1+exp(i*x)))-1)

6   Pass
x = 0.0263; [c,s] = infinite_series(x); c_correct = 0.9574346130196565; s_correct = 0.1214323234202421; assert(abs(c-c_correct)<50*eps & abs(s-s_correct)<50*eps)

fs = function_handle with value: @(x)0.5i*exp(-i*x)*(-1+exp(i*x))*(-exp(i*x)+exp(i*x)*log(1-exp(i*x))+log(exp(-i*x)*(-1+exp(i*x)))-1)

7   Pass
x = 6.273; [c,s] = infinite_series(x); c_correct = 0.9837633160098646; s_correct = -0.0568212139709541; assert(abs(c-c_correct)<50*eps & abs(s-s_correct)<50*eps)

fs = function_handle with value: @(x)0.5i*exp(-i*x)*(-1+exp(i*x))*(-exp(i*x)+exp(i*x)*log(1-exp(i*x))+log(exp(-i*x)*(-1+exp(i*x)))-1)

8   Pass
x = 31/7; [c,s] = infinite_series(x); c_correct = -0.2961416175321223; s_correct = 0.3148962998550185; assert(abs(c-c_correct)<50*eps & abs(s-s_correct)<50*eps)

fs = function_handle with value: @(x)0.5i*exp(-i*x)*(-1+exp(i*x))*(-exp(i*x)+exp(i*x)*log(1-exp(i*x))+log(exp(-i*x)*(-1+exp(i*x)))-1)